Pendampingan dan Pemberdayaan Masyarakat Peduli Hutan Kemasyarakan Wana Lestari Desa Bukit Tinggi, Kecamatan Gunung Sari, Kabupaten Lombok Barat - Markum; Umar Nasir; Misdarti; Alfian Pujian Hadi; Firman Rahman; Ismawati; Suyono (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Community forestry is the active participation of the community in forest management and conservation as a potential management model to overcome the problems of deforestation and environmental degradation. This service aims to provide assistance to the people of Bukit Tinggi Village to increase their capacity to manage forests effectively and sustainably. The service method is carried out through discussions with the Gapoktan Wanalestari group, discussions with the Head of Bukit Tinggi Village and the BPD, and field observations of the Gapoktan Wanalestari location. Apart from that, interviews with community forest managers, field officers and local stakeholders can also be conducted to gain understanding regarding the concept of good community forest management. The results of service activities show that the condition of forest cover is still good, dominated by mahogany plant cover, the result of watershed rehabilitation in 2000, through a labor-intensive pattern, with the plants for watershed rehabilitation being mahogany and sono keling. Mahogany growth is very high, while according to farmers, sengon growth only reaches 10% success. Gapoktan has also contributed PNBP, by making regular deposits since 2021 amounting to IDR 6 million/year. The PNBP is obtained from the sharecropper's contribution which is charged per acre at IDR 2,000/year. Apart from that, there are 3 strategic potential values ​​possessed by the people of Bukit Tinggi Village, namely (1) the potential value of developing forest product resources (NTFPs) which are currently being cultivated by farmers, including durian, sugar palm, duku, coffee; (2) potential for developing environmental services, namely ecotourism in forest areas and clean water; (3) potential for tourism development at Meninting Dam.